Gambaran Umum Faktor Risiko Covid-19 pada Tenaga Kesehatan Rumah Sakit di Asia - Narizma Nova; Wiku Bakti Bawono Adisasmito (Jurnal Health Sains, 2021)
In 2020, nearly 300,000 health workers who were infected and died due to Covid-19 around the world including Asia. Several countries in Asia are among the top 10 of the highest healthcare workers deaths in the world. When the rate of infection and hospitalization increases, health workers must be prioritized so that they are not drained by the Covid-19 infection. Health workers are at a high risk level for exposure to the Covid-19 while they hold an important roles of handling the Covid-19 case. This systematic review aims to analyze the risk factors of health workers in hospitals among Asian Countries regarding Covid-19. We searched, from Science Direct, Springerlink and Pubmed identify relevant studies from 2020 on the topic of risk factors of transmission Covid-19 among healthcare workers in hospital of Asian Countries. From these searches, a total of 135 papers were identified of which 22 studies met criteria. The main results were about risk factors for health workers in hospitals during Covid-19 such as personal protective equipment (PPE) availability, exposure to infected patients, excessive workload, IPC training, pre-existing medical conditions and psychological factors. The level of knowledge of health workers about Covid-19 is classified as good, but factors such as job categories, work experience affect their attitudes and behavior so that the factors of anxiety, fatigue and stress are quite varied. It takes considerable efforts and strategies especially from the work place so that the risk factors from health workers can be overcome.